Teacher Truancy in India: The Role of Culture, Norms and Economic Incentives - Kaushik Basu (BREAD Working Paper No. 112, 2006)
Social scientists often emphasize how `culture' and `social norms' can be important determinants of economic behavior and development. This raises questions of the relative importance of economic incentives and these other more social variables, like culture, and of how they interact with one another. This paper uses some recent stylized facts concerning the problem of teacher truancy in India and constructs a simple model to illustrate the interaction between the `economic' and the `social.' It discusses how this enriches our view of policy-making for improving economic performance.